Policy diffusion within international organizations: A bottom-up analysis of International Monetary Fund tax work in Panama, Seychelles, and the Netherlands - Matti Ylönen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
I analyse the evolution of the International Monetary Fund tax policy advice in three countries commonly used for tax evasion or avoidance: Panama, Seychelles, and the Netherlands. A review of loan agreements and Country Reports covering 1999 to 2017 highlights the dependence of the Fund's country teams on external assessments produced by the Fund's other departments and smaller international organizations. Insofar as the Fund has paid attention to international tax flight, its focus has largely been on individual-level tax evasion instead of corporate tax avoidance. The responses have been inconsistent, with the tax haven regime of Seychelles getting much more attention than Panama and the Netherlands.
Keywords: F23; F33; F34; F53; F55; H26; 330; International Monetary Fund; Financial Action Task Force; OECD; tax avoidance; taxevasion; sovereign debt